آليات التجديد الأصولي عند الإمام الشافعي Fundamentalist Renewal Mechanisms According To Imam Al-shafi’i - أيمن, بولمعالي; محمد, مزياني (جامعة الوادي university of eloued, 2023)
إن شأن العلوم أن تخضع لأطوار متفاوتة، تصقل مباحثها، وتثري مضامينها، وتهذب مشكلاتها، وبين فينة الطور والطور قد تظهر نقلة من بنيات فكر عالم تحوي نظرة تجديدية تمايز سالفتها في المنهج والمدرك، وكذلك الحال مع علم أصول الفقه والإمام الشافعي، فقد حصل له أن جالس أعلام الفن من سابقيه، فأخذ من كل مدرسة نبذا مما رآه صالحا، وترك نتفا مما رآه طالحا، فخلص إلى منهج تجديدي لعلم أصول الفقه عريت عنه تصرفات السابقين ضمنه كتابه الرسالة الذي يعد أول تصنيف مستقل في علم أصول الفقه، وقد استند الإمام على آليات ومسالك مكنته من تجسيد نظرته التجديدية، ليبرز أصول الفقه علما قادرا على معالجة قضية تناهي النصوص وتوالي المستجدات، مما يعزز مقصد الوظيفة العملية التي قام لبغيتها. Sciences are subject to various stages that refine their topics and enrich their contents and in between these stages, a shift to a renewal view may appear from time to time. For instance, the science of jurisprudence has witnessed refinement especially with Imam Shafi’i, who has benefited from his predecessors and took from each school what could be helpful in the development of the science. Therefore, he managed to make a new method in the science of jurisprudence different from that adopted by his predecessors, and included that method in his book The Message, which is the first independent classification in the science of jurisprudence, in which he realized his view that allowed the science of jurisprudence to deal with different issues and text and thus achieve the objectives of the study
مقال
Keywords: آليات؛ تجديد؛ الأصول؛ الشافعي؛ النص; Mechanisms; Renewal; Assests; Shafi’i; Text.